2008
DOI: 10.1111/j.1464-410x.2008.07435.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the role of cytokine therapy in advanced renal cell carcinoma

Abstract: Tribute to Professor Pieter De Mulder, from Martin Gore Pieter and I were often pitted against each other in debates at international meetings on the role of cytokine therapy. The truth is that there was little disagreement between us, but we both thought such set pieces were a good way to highlight the issues surrounding the use of cytokines. He wanted our true joint view to be put on record, and the result is this article. Pieter himself suffered from kidney cancer for many years and he died in April as we w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…(1) Metastatic disease is present in around 30% of RCC patients when diagnosed, and 30-40% of patients with earlystage disease relapse with metastases following nephrectomy. Renal cell carcinoma is highly resistant to conventional cytotoxic chemotherapy and the prognoses in patients with metastatic RCC (mRCC) are poor, (2) with a median overall survival (OS) period of approximately 1 year (3) and a 5-year survival rate of <10%. (4) Immunoreactive cytokines, interferon-a (IFN-a) and interleukin-2 (IL-2) were the treatment mainstay for mRCC.…”
mentioning
confidence: 99%
“…(1) Metastatic disease is present in around 30% of RCC patients when diagnosed, and 30-40% of patients with earlystage disease relapse with metastases following nephrectomy. Renal cell carcinoma is highly resistant to conventional cytotoxic chemotherapy and the prognoses in patients with metastatic RCC (mRCC) are poor, (2) with a median overall survival (OS) period of approximately 1 year (3) and a 5-year survival rate of <10%. (4) Immunoreactive cytokines, interferon-a (IFN-a) and interleukin-2 (IL-2) were the treatment mainstay for mRCC.…”
mentioning
confidence: 99%
“…At present, the most widely used regimens for metastatic RCC (mRCC) are cytokine therapies, including interferon-alfa and interleukin-2, which in previous studies showed response rates of only 10–20% and resulted in debilitating adverse effects [5], [6], [7]. Studies of cytokine therapies with or without chemotherapy have shown short-term partial response rates of up to 20–35% [8], [9]. New treatments are needed to develop strategies for controlling metastatic disease and improving quality of life.…”
Section: Introductionmentioning
confidence: 99%